The Local Wisdom of Floating Market Traders in Supporting Honest and Fair Trade - Yuli Apriati; Dasim Budimansyah; Chairil Faif Pasani; Encep Syarief Nurdin (Jurnal Ilmu Sosial dan Humaniora, 2024)
Although in traditional trade practices, unethical practices are increasingly occurring, characterized by a lack of principles of honesty, trustworthiness, and transparency among traders, on the contrary, in traditional river-based trade practices at the Lok Baintan floating market with local wisdom "kuranglabih" can realize these practices. Fairtrade is in line with Islamic values. This research aims to describe trading ethics based on Islamic values in trading practices on the floating market and analyze the integration of Islamic values, local wisdom, and the role of Panyambangan in traditional river-based trade at the Lok Baintan Floating Market. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews, and documentation to record cultural phenomena comprehensively. The research results show that it has contributed significantly to the Banjar people's cultural richness and character formation. As well as making strong river-based trade practices to support honest and fair trade. Local wisdom kuranglabih reflects ethics, kinship, tolerance, justice, mutual respect, and economic aspects. As moral guides, Miners play an essential role in spreading the values of honesty and generosity among traders. Commitment to Islamic values shows how cultural heritage can develop without losing its essence. This research contributes to understanding the importance of local wisdom in building honesty and justice. Research implications include sustainable planning for policymakers to protect traditional river-based markets and efforts to empower traders in developing and maintaining trade in floating markets.